(untitled) (Research, Society and Development, 2021)
The outbreak of coronavirus disease (COVID-19) and its rapid spread along with the ease of transmission, the National Health Council established social distancing and, with this, there was a need for prophylactic measures such as remote teaching-learning. The study aims to investigate the adaptation of nursing course professors in the use of remote technologies during the pandemic and to quantify the level of adaptation through comparative self-assessment. This is a mixed, descriptive and exploratory study, under CAAE 42315120.2.0000.8044 and opinion number 4.552.435, having as a source of information the research through an online form sent by email to the professors of the higher nursing course who teach or have taught in the nursing course of the private education institution, located in metropolitan region I of Rio de Janeiro. It is concluded that, at the beginning of the pandemic, there was a great institutional change and a challenging adaptation process with new technologies and that, currently, teachers still face difficulties in this remote teaching-learning process and do not feel 100% adapted to the current pandemic scenario of institutions.